Letter (copy) : Assistance for Spanish workers' children - Tewson, Vincent
032-0189-001 International. HVT/WJR/AT/264 1st December, 1938. Mr. W. Schevenels, International Federation of Trade Unions, 9 Avenue D'Orsay, Paris, VII. Dear Comrade Schevenels, ASSISTANCE FOR SPANISH WORKERS' CHILDREN We have received a letter from the Department d'Economia, Barcelona, suggesting that endeavours be made to brighten Christmas time for the children of the Spanish workers. A similar letter has been received also by Mr. Elvin, Chairman of the last Trades Union Congress. We are sending you herewith one of the letters, for your consideration. Perhaps you would like to consult with Comrade Santiago, in order to see whether it is possible to fit the idea into the scheme of help which it is the purpose of the International Solidarity Fund to carry out. Meanwhile, you can rest assured that all our efforts are being strenuously maintained to continue the distribution of milk and other food and clothing among those innocent victims of the war. Yours faithfully, Assistant Secretary. 292/946/32/189